OBSERVATIONS ON THE FISHERY AND BIOLOGY OF GRAMMOPLITES SCABER (LINNAEUS) - Kuthalingam, M D K (Indian Journal of Fisheries, 2011)
A preliminary study of the fishery and biology of Grammoplites scaber was made based on the landings of M.V. Tarpon during the years 1962-64. Higher catch rates (40.4 - 62.4 kg/hr) were obtained in depths 40-55 m and in shallower waters the catch rates were poor (6.2-20.4 kg/hr); also the larger size groups of fishes occurred in deeper waters. The sex ratio differed considerably according to depths. G. scaber feeds predominantly on crustaceans and the prawn Parapenaeopsis stylifera appears to be the favourite food of the fish above 142 mm.